Pd schottky contacts on sol-gel derived ZnO thin films with nearly ideal richardson constant - Yadav A.B.; Pandey A.; Jit S. (My University, 2025)
his letter reports the temperature-dependent analysis of measured I-V characteristics of Pd/ZnO thin filmbased Schottky diodes grown on n-Si (100) substrates by sol.gel method. Assuming a Gaussian distributed barrier height at the Pd/ZnO interface with a standard deviation (σ0) around a mean barrier height q&phiB,m, the analysis estimates the value of Richardson constant ∼-31.67 Acm-2K-2, which is not only very close to its theoretical value of ∼-32 Acm-2K-2 (for m.e = 0.27m0), but also the best result reported so far for ZnO-based Schottky contacts. The estimated value of the zero-bias mean barrier height (∼1.39 eV) at T = 0 K is also observed to be very close to its theoretical value of 1.42 eV (for work function of Pd = 5.12 eV and electron affinity of ZnO = 3.7 eV). © 2014 IEEE.